The implementation of the concept of environmental carrying capacity into spatial management of cities: A review - Świąder, Małgorzata (Management of environmental quality, 2018)
PurposeUncontrolled and unsustainable urban development has a significant impact on the overall quality of the environment. Contemporary spatial management does not take into account the non-economic conditions of ecosystem functions and their biophysical limits, which results in a deterioration of the environment. Furthermore, urban development continues all over the world, which is associated with a projected population increase, particularly in cities. Therefore, there is need to include analyses in the field of environmental carrying capacity (ECC) for more sustainable spatial management and development. The ECC concept is a tool for sustainable development of human settlements. It could be defined as threshold level of anthropopressure, which the environment is able to balance and withstand without serious degradation and irreversible changes. The use of ECC assessment will help ensure the needs of the city’s residents, which are conditioned by the environment. The paper aims to discuss this issue.Design/methodology/approachThis review study presents an overview of the ECC concept and its potential for use in spatial management at local level, especially for cities. The content analysis introduces definitions of spatial management and others main actions of spatial economy as well as the definitions of ECC. The overview of existing ECC models is a part of presented review.FindingsThe paper shows the ECC approach from global to local level on Poland as an example country.Originality/valueThe literature review identified that the idea of ECC could be a useful concept and tool for sustainable spatial development and management. This concept allows for verification of the resources and environmental state of given territory unit. Therefore, the assessment of ECC allows to verify if development of given area, for instance country, region or even city, is conducted within the framework of sustainable principles. Despite this, the assessment of ECC is not taken into account when future spatial management is defined. Thus, this circumstance could be a reason for this research area development.